Vídeo corporativo motivacional: agenciamentos simbólicos nas organizações - Bastos, Laércio Gomes (2010)
This research aimed to study the motivating potential of corporate videos and symbolic assemblages that occur through this kind of audiovisual media. We intended to classify the different approaches and persuasive strategies in order to build the mapping of the symbolic universe inherent in corporate culture, since this is the environment where the corporate motivational video is produced and presented. We tried to identify the reasons why the language patterns for this kind of video have remained unchanged in the recent years despite of the advances of the technologies of intelligence. Mainly supported by the studies by Joseph Nuttin, Cecilia Bergamini, Pierre Lévy, Lucia Santaella and Harry Pross, this study examines the symbolic and ritual assemblages surrounding the creation, production and presentation of corporate motivational videos through the theoretical approach of psychology, semiotics and media. This work wishes to provide new points of view for motivation in corporative organizations